Measuring heart rate variability using a heart rate monitor in horses (Equus caballus) during groundwork - Kapteijn, Chantal M.; Frippiat, Thibault; van Beckhoven, Cees; van Lith, Hein A.; Endenburg, Nienke; Vermetten, Eric; Rodenburg, T. Bas (Frontiers in Veterinary Science, 2022)
Measuring physiological parameters of stress in horses during groundwork, for example when involved in equine-assisted interventions, is important to gain insight into the stress levels of the horses. Heart rate and heart rate variability can be used as physiological indicators of stress in horses. Heart rate monitors could be easily incorporated into practice, as they are not expensive and easy to use. However, it is questionable whether heart rate monitors present accurate heart rate variability results in exercising horses, similar to electrocardiograms. The aim of this study was to determine the accuracy of heart rate monitors for the assessment of heart rate variability in horses during groundwork exercise. Simultaneous telemetric electrocardiograms (Televet) and heart rate monitor (Polar H10 transmitter and M430 receiver, Hylofit electrodes) recordings were performed on 28 horses (15 mares and 13 geldings). Results indicate that the heart rate monitor system accurately determined heart rate and time-domain heart rate variability parameters when compared to electrocardiograms during both baseline and groundwork conditions. As expected, heart rate significantly increased and the heart rate variability significantly decreased during groundwork compared to baseline conditions. This indicates that the heart rate monitor can be used to accurately determine heart rate variability during groundwork.